2019
DOI: 10.1016/j.ast.2019.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thickness-to-chord ratio on aerodynamics of non-slender delta wing

Abstract: , 84 pages Flow characterization over delta wings have gained attention in recent decades due to their prevailing usage in designs of unmanned air vehicles (UAVs). In literature, only a few studies have reported wing thickness effect on both the aerodynamic performance and detailed flow structure over delta wings. In the present investigation, the effect of thickness-to-chord (/) ratio on aerodynamics of a non-slender delta wing with 45 degree sweep angle is characterized in a low-speed wind tunnel using laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In another numerical calculation, Synthetic jet control of the asymmetrical flow field of the flying wing for an UAV was investigated and the study showed that synthetic jet control cannot effectively improve the effect of asymmetrical vortex on the lateral aerodynamic characteristic of the model in zero sideshift [14] on the other hand, in a PIV experiment system, The flow structures and aerodynamic performance of a thin delta wing with a sweep angle of 65 degrees are equipped with needle vortex generators was studied and findings were compared with smooth wing [15] study showed that the acicular wing delays eddy distortion compared to a straight wing. In a wind tunnel experiment, the effect of the thickness-chorus (t/C) ratio on the aerodynamics of a non-thin delta wing with a sweep angle of 45 degrees was characterized and results indicated that the effect of ratio on flow structure was quite substantial [16].…”
Section: Introductionmentioning
confidence: 99%
“…In another numerical calculation, Synthetic jet control of the asymmetrical flow field of the flying wing for an UAV was investigated and the study showed that synthetic jet control cannot effectively improve the effect of asymmetrical vortex on the lateral aerodynamic characteristic of the model in zero sideshift [14] on the other hand, in a PIV experiment system, The flow structures and aerodynamic performance of a thin delta wing with a sweep angle of 65 degrees are equipped with needle vortex generators was studied and findings were compared with smooth wing [15] study showed that the acicular wing delays eddy distortion compared to a straight wing. In a wind tunnel experiment, the effect of the thickness-chorus (t/C) ratio on the aerodynamics of a non-thin delta wing with a sweep angle of 45 degrees was characterized and results indicated that the effect of ratio on flow structure was quite substantial [16].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, non-slender wing having low to moderate sweep angle (Λ ≤ 55°). Most of the delta wing UAV has been designed in the non-slender configuration (Gursul et al , 2005; Brett and Ooi, 2014; Ghazijahani and Yavuz, 2019). Therefore, the study of non-slender delta wing is important for future UAV development.…”
Section: Introductionmentioning
confidence: 99%
“…The UAV industry is growing rapidly, including the delta-planform UAVs. Therefore, many studies have been conducted to study the effects of flow control on the delta wing [11]. Flow control techniques (active and passive) had been implemented on the delta wing to improve the vortex properties and delay the vortex breakdown [12].…”
Section: Introductionmentioning
confidence: 99%